KINERJA PEGAWAI DIKAJI DARI KEPEMIMPINAN, BUDAYA ORGANISASI DAN MOTIVASI - Khayatun, Siti; Hartarini, Yovita Mumpuni; Triasningrum, Frida Widyawati (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to find out how much influence Leadership, Organizational Culture and Motivation have on Employee Performance at the Education and Culture Service in Pati Regency. The population in this study were employees Performance at the Education and Culture Service in Pati Regency who were present at the time of data collection, namely 94 employees Performance at the Education and Culture Service in Pati Regency. The collection technique uses accidental sampling, which is a method of determining samples by taking respondents who happen to be present or available in a place according to the research context. The research method used is multiple linear regression analysis method, partial testing (T test), model significance testing (F test) and coefficient of determination testing (R²). The results of this research show a leadership regression coefficient value of 0.204. Meanwhile, the Tcount value is 3.638>Ttable 1.987 and the sign is 0.000, Organizational Culture is 0.553. Meanwhile, the Tcount value is 13.789>1.987 and Motivation is 0.411. Meanwhile, the T value is 6.331> 1.987 and the sign is 0.000. Based on the test results, the coefficient of determination R2 is 77.1%. This means that the relationship between leadership, organizational culture and motivation has a positive and significant influence on employee performance at the Department of Education and Culture in Pati Regency. This can be proven in the F test of F count 101.166> F table 2.70 with a significance figure = 0.000 at Department of Education and Culture in Pati Regency. Leadership is influential in maintaining optimal employee performance, so it is recommended that you continue to implement and maintain good leadership, Organizational Culture within the organization so that employees Performance at the Education and Culture Service in Pati Regency are able to be motivated when their leadership is good in all respects, because in an organization or agency the decision remains in the hands of the leader.